Media Release: Jane Tolmach for Assembly (1975)
This October 8, 1975 media release announces the formation of the Jane Tolmach for Assembly Committee and invites volunteers of all backgrounds to join the campaign. It highlights Tolmach's experience in local government and her record of listening to and advocating for Ventura County residents. The statement emphasizes her commitment to keeping government accountable and closer to local control, opposing the concentration of decision-making power in Sacramento. Tolmach also pledges to resist shifting state financial burdens onto local property taxpayers and to work toward establishing a four-year college in Ventura County. The release portrays her as accessible, dedicated, and focused solely on representing the interests of local citizens.